Determinants of job satisfaction among employees at Kuching High Courts /Aida Montong - Montong, Aida (2018)
Determines the job satisfaction level of employee is basic to job satisfaction. It is an essential component that can influence the employees' performance and aggregate administration conveyance in the organization. The independent variables for this study are determinants (working environment, career development, motivation, leadership, and teamwork), while the dependent variable is the job satisfaction of the employees. The main objective of this study is to decide the level objective satisfaction among employees at Kuching High Court. The second objective is to look at the relationship between the determinants (working environment, career development, motivation, leadership, and teamwork) and job satisfaction. The third objective is to explore the primary determinant that impacts the employees job satisfaction. From the examination, mean and standard deviation demonstrate the abnormal state of job satisfaction among employees in Kuching High Court. Consequently, this examination had acknowledged the theory to quantify the abnormal state of objective satisfaction among workers in Kuching High Court. From the investigation Pearson's Correlation, determinants (working environment, career development, motivation, leadership, and teamwork) had a noteworthy positive connection with the dependent variable (Job Satisfaction). Consequently, this investigation had acknowledged the theory there is a critical connection amongst determinants and job satisfaction. For the various relapse examination, it demonstrated that working environment as the fundamental indicator influencing employees job satisfaction in Kuching High Court. Thusly, this examination had acknowledged speculation the main determinant of employee job satisfaction is working condition